Enhancing the environment of paediatric oncology unit the Malaysian way: Review, revive, recommend - Mohd Nawawi, Norwina; Chiam, Tat Hong; Sanusi, Aliyah Nur Zafirah; Md Alwi, Ahmad Naufal (2017)
Cancer cases are on the rise in Malaysia with occurrence felt in almost every household. Cancer is the 9th admitted cases and the 3rd causes of death in the Ministry of Health Malaysia hospitals (MoH,2016). Children are not exempted. Extended Caregivers (E-CGs) , including parents, upon diagnosed, had to change their lifestyle abruptly. Some take leaves from work and schools. They need to frequent the designated hospitals every other day for their children's treatment, to give support and encouragement. This move, inevitably, make hospitals their 2nd home. Malaysia is home to multi-ethnicity and multi-religious population. Cancer diagnosis in their love ones creates anxiety and depression. Although there were many researches made to support the caregivers with caring environment and services, however due to the aged facility and lack of budget, current paediatric oncology unit lack the spatial compassionate care environment for both patients as well as their caregivers. This research reviews the potential of selected existing paediatric oncology facilities of a hospital with the intention of providing pragmatic recommendation for its immediate enhancement. The aim is to enable patients and their caregivers to experience bearable stay in the hospital while treatment goes on. Explorative method is adopted for this research. Selected hospitals with paediatric oncology unit were visited, observed and participants interviewed, as case studies. Analysis was conducted through trending and comparison with demands on designs required for paediatric oncology unit, made. The design proposals are preliminary outcomes and subject to respective hospital management’s approval of its implementation. Care has to go on. General findings denote how Malaysians, despite all odds, in the spirit of a common vigilance of their love ones, still have a way to make a home away from home, through creative improvisation.